A Novel Approach to Locating Community Clinics to Promote Health Care Accessibility and Reduce Health Disparities in Baltimore, Maryland - Caitlin DeClercq PhD; Mohammad Gharipour PhD; Salman Mohagheghi PhD; Andrew Tot Bui MArch; Naomi Wong Hemme MArch; Eric Johnson Bsc (SAGE Publishing, 2023)
Baltimore, Maryland's entrenched racial residential segregation renders the city's world-class medical facilities and services inaccessible to many Black residents living in its most divested neighborhoods. Arguing the need for post-pandemic health care facilities to address health inequities as a practice of care-giving, this article describes a project funded by the National Institutes of Health (NIH) to define a novel, transdisciplinary methodology for identifying ideal vacant sites for conversion into community clinics in Baltimore's most vulnerable neighborhoods. Positioning architecture as a social determinant of health, this paper suggests ethical and methodological reorientations toward a compassionate approach to clinic design and placement.